Análisis del beneficio de la producción de hortalizas en el sector rural - Hernández Echeverría, Guadalupe Edelmira (2022)
The implementation of vegetable production in rural areas is a benefit for the communities, that is, through planting a healthy and good quality horticultural product is obtained. The production of vegetables is an alternative to alleviate the family economy, since it would generate income from the sale of surplus production and a decrease in family spending for self-consumption. To optimize the production of vegetables you can cover the expenses with recyclable materials inside the homes and even have a planting schedule you can see what type of crop is used. As a result, we obtain that the production of vegetables in rural areas is a sustainable benefit by promoting savings to family spending for the food item in families in rural sectors. To obtain vegetative products we must consider that the fruit is of good quality, additional can be generated by giving added value to vegetables. Through horticultural gardens, socio-economic benefit for the rural sector is promoted. The benefits of food safety are diverse with home gardens that manage to produce quality food and good taste throughout the year or for several months. A well-established garden can cover the family's food demand with its production, which represents significant savings; And with the sale of some products from the garden, it helps to improve family income and acquire inputs, such as seeds or other materials.